Does Political Dynasty Cause Poverty? - Guritno, Danur Condro; Samudro, Bhimo Rizky; Soesilo, Albertus Magnus (Universitas Negeri Semarang, 2018)
The delegation of central government authority to local governments can encourage policy or program targeting to be more targeted because it is indispensable for poverty reduction. Education and health are considered to be capable of alleviating poverty. This paper aims to find out the amount of budget based on Act no. 20/2003 Article 49 on National Education System (Sisdiknas) and Act no. 36/2009 Article 171 on Health in the area of political dynasty of regeneration type (vertical) and to find out the average decrease or increase of poverty rate per year in regional of political dynasty. This is descriptive research, using the ratio analysis of regional expenditure per function. This paper shows that during the period of 2005-2017, all the allocations of regional education budget of political dynasties (regeneration type) have been in accordance to the law. While the allocation of health budget, there are 3 regions from 12 regions of political dynasty that have not fulfilled the law, in addition, the area of political dynasty is able to reduce poverty with an average decrease of 0.2% -1.5% per year, and based on the average national poverty is 8 out of 12 regions of political dynasty in the poor category.